Fence. Volume five, Rise - Pacat, C. S. (BOOM! Box, 2022)
En Garde! Excitement is in the air as Nicholas and his friends celebrate their prestigious invitation to the Halverton Training Camp. But they soon find themselves pushed to their limits as they come face-to-face with the best teams in the country. Will a new addition to the opposing team help Nicholas awaken the fighting spirit he needs to prevail? And what will it mean for his friendship with Seiji?